Negative active material and preparation method thereof, pole piece and battery

By adopting amorphous phase anode active material with the chemical formula AxTMyChDb, the problems of insufficient energy density and safety of lithium batteries are solved, high energy density and stability are achieved, and degradability is achieved in water environments.

CN119905579AActive Publication Date: 2025-04-29SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510118859.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-29
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The energy density of existing lithium batteries is not high enough, resulting in poor battery life of electric vehicles, and the negative electrode material is easily caused by volume expansion and safety problems after high lithium is embedded.

Method used

An anode active material with the chemical formula AxTMyChDb is used, where A is lithium and/or sodium, TM is a transition metal, Ch is a chalcogen element, D is O or BaC1-a, B and C are negative valence anions and anion clusters. The negative electrode active material has an amorphous phase, and the mass proportion of the amorphous phase is not less than 10%. This material is obtained by amorphizing treatment and has good stability and safety.

Benefits of technology

It significantly improves the energy density and cycle stability of lithium batteries, reduces the risk of volume expansion and safety, and is degradable in water environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905579A_ABST
    Figure CN119905579A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode active material and a preparation method thereof, a pole piece and a battery, and relates to the field of batteries. A is lithium and / or sodium, TM is a transition metal, Ch is a chalcogenide element, D is O or BaC1-a, B is selected from at least one type of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one type of negative trivalent anions and negative trivalent anion clusters, 0.5 < = x < = 8, 0.8 < = y < = 1.1, 0.25 < = a < = 0.75, 0.8 < = b < = 1.2; the negative electrode active material has an amorphous phase, and the mass ratio of the amorphous phase in the negative electrode active material is not less than 10%. The technical problem that an existing negative electrode active material cannot give consideration to high capacity, low expansion and high safety at the same time can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a negative electrode active material and a preparation method thereof, a pole piece and a battery. Background Art

[0002] Lithium batteries have been widely used in consumer electronic devices and new energy electric vehicles due to their high energy density and long cycle life. However, the rapid development of electric transportation and large-scale energy storage has put forward higher requirements for lithium batteries.

[0003] At present, the energy density of lithium batteries is not high enough, resulting in poor endurance of electric vehicles, which is difficult to meet the requirements of medium and long-distance transportation. Therefore, it is necessary to further improve the energy density of lithium batteries. Electrode active materials are the key to determining the upper limit of battery energy density. Current research on negative electrode materials mainly focuses on graphite negative electrodes, lithium titanate negative electrodes, silicon-based materials, etc. However, the capacity of graphite negative electrodes and lithium titanate negative electrodes is relatively low. Among them, the actual use capacity of graphite negative electrodes does not exceed 350mAhg -1 , and high current charging easily leads to metal lithium deposition, which can cause battery damage and safety issues. The capacity of lithium titanate negative electrode is lower, and the actual capacity is less than 170mAhg -1 , and titanium-based materials are more expensive. Silicon-based negative electrode materials have a higher theoretical specific capacity, up to 3000mAhg -1 However, the high lithium embedding amount will lead to severe volume expansion of the electrode, causing pulverization of the electrode material and continuous rupture and regrowth of the SEI film, and the battery performance will continue to decay; and whether it is graphite or silicon-based, on the one hand, it is very easy to cause safety accidents after thermal runaway when encountering water; on the other hand, it is extremely active after lithium embedding. When the battery is damaged or disassembled, the lithium-embedded negative electrode will react with moisture in the air and release heat violently when exposed to air, which is also easy to cause thermal runaway and safety accidents. Summary of the invention

[0004] In view of the above problems, the present application provides a negative electrode active material and a preparation method thereof, an electrode sheet and a battery, which can improve the technical problem that the existing negative electrode active materials cannot take into account high capacity, low expansion and high safety.

[0005] In a first aspect, the present invention provides a negative electrode active material, the chemical formula of the negative electrode active material is A x TM y ChD b , where A is lithium and / or sodium, TM is a transition metal, Ch is a chalcogen element, and D is O or B a C 1-a, B is selected from at least one of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one of negative trivalent anions and negative trivalent anion clusters, 0.5≤x≤8, 0.8≤y≤1.1, 0.25≤a≤0.75, 0.8≤b≤1.2;

[0006] The negative electrode active material has an amorphous phase and the mass proportion of the amorphous phase in the negative electrode active material is not less than 10%.

[0007] In the technical solution of the embodiment of the present application, the negative electrode active material has an amorphous phase and the mass proportion of the amorphous phase in the negative electrode active material is not less than 10%. On the one hand, the amorphous material has the isotropic volume change characteristic, which can significantly reduce stress concentration. At the same time, the microstructure is relatively loose, which can alleviate volume expansion. In addition, ions do not need to cross grain boundaries in the amorphous material and can move more easily in the amorphous structure, which is beneficial to increase the ion diffusion rate. In addition, due to its amorphous structure, the amorphous material can accommodate more lithium / sodium ions and increase the battery capacity. On the other hand, the anti-perovskite or double anti-perovskite amorphous material of the above general formula has good stability and safety under different lithium deintercalation states, reacts mildly with water, does not burn or explode, and has no toxic or harmful products. It can be used for water-degradable batteries or water-soluble batteries in an environment containing water or aqueous solutions, such as water-degradable batteries or water-soluble batteries in an ocean or humid environment.

[0008] In some embodiments, the mass percentage of the amorphous phase in the negative electrode active material is not less than 30%.

[0009] Optionally, the negative electrode active material is in an amorphous phase.

[0010] In some embodiments, 1.9≤x≤2.1; and / or, 0.9≤y≤1.1; and / or, 0.45≤a≤0.55; and / or, 0.9≤b≤1.1.

[0011] In some embodiments, D is O, b=1; or, D is B a C 1-a , 1≤x≤2.5, which can be optionally 1.9≤x≤2.1.

[0012] In some embodiments, the TM includes at least one of Fe, Co, Mn, Ni, Cu, Cr, V, Ti, W, Si, Sn, Nb, and Mg.

[0013] In some embodiments, Ch includes at least one of S, Se, and Te.

[0014] Optionally, B includes F - , Cl - Br - ,I- , H - OH - 、BH4 - NH2 - 、NO2 - and CN - At least one of.

[0015] Optionally, C includes N 3- 、(PO4) 3- 、(SbO4) 3- and (AsO4) 3- At least one of.

[0016] In a second aspect, the present application provides a method for preparing the negative electrode active material provided in the first aspect of the present application, comprising: obtaining an antiperovskite material characterized by a chemical general formula, performing an amorphization treatment on the antiperovskite material to obtain a negative electrode active material;

[0017] The amorphization treatment includes: making a working electrode by mixing an antiperovskite material and a conductive agent, assembling it with a counter electrode into a liquid half-cell, and then discharging the liquid half-cell at a constant current to remove element A to obtain an amorphous phase, wherein element A is Li and the counter electrode is lithium metal, or element A is Na and the counter electrode is lithium metal.

[0018] In the technical solution of the embodiment of the present application, the above method can perform amorphization treatment on the antiperovskite material, and the negative electrode active material obtained by the above method can stably exist and carry out electrochemical reactions compared to the negative electrode active material prepared by the ball milling solid phase method, and the first coulombic efficiency is significantly improved, and the battery cycle stability is effectively enhanced.

[0019] In some embodiments, the preparation method further comprises: performing constant current charging on the liquid half-cell having the amorphous phase to obtain a lithium / sodium-rich negative electrode active material.

[0020] In a third aspect, the present application provides a pole piece, which includes an active material layer, and the active material layer includes the negative electrode active material provided in the above embodiment.

[0021] In a fourth aspect, the present application provides a battery, which includes the electrode in the above embodiment.

[0022] Optionally, the battery comprises a water-degradable battery.

[0023] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0025] Figure 1 XRD pattern of the negative electrode active material prepared in Example 1;

[0026] Figure 2 XRD pattern of the negative electrode active material prepared in Example 2;

[0027] Figure 3 XRD pattern of the negative electrode active material prepared in Example 3;

[0028] Figure 4 XRD pattern of the negative electrode active material prepared in Example 5;

[0029] Figure 5 Li2FeTe(N 0.5 Cl 0.5 )||The first cycle charge and discharge curve of Li half-cell;

[0030] Figure 6 XRD pattern of Li2FeSO prepared in Comparative Example 1;

[0031] Figure 7 XRD pattern of Li2FeSeO prepared in Comparative Example 2;

[0032] Figure 8 XRD pattern of Li2CoSeO prepared in Comparative Example 3;

[0033] Fig. 9 XRD pattern of LiFeSO prepared in Comparative Example 4;

[0034] Fig.10 XRD pattern of LiFeSO prepared in Comparative Example 5;

[0035] Fig.11 is the charge and discharge curve of the first LiFeSO||Li half-cell;

[0036] Fig.12 is the charge and discharge curve of the second LiFeSO||Li half-cell;

[0037] Fig.13 is the charge and discharge curve of the third LiFeSO||Li half-cell;

[0038] Fig.14This is the first cycle charge and discharge curve of the Li5FeSO||Li half-cell;

[0039] Fig.15 This is the first cycle charge and discharge curve of the Li5FeSO||Na half-cell;

[0040] Fig.16 This is the first cycle charge and discharge curve of the LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state battery under 60℃ test conditions in the voltage range of 0.5-4.2V;

[0041] Fig.17 This is the first cycle charge and discharge curve of the LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state battery under 60℃ test conditions in the voltage range of 0-4.6V;

[0042] Fig.18 This is the charge and discharge cycle curve of the LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state full battery under 60°C test conditions and in the voltage range of 0.5-4.2V. DETAILED DESCRIPTION

[0043] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0045] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0046] The inventors have found that for the chemical formula A x TM y ChD b (A is lithium and / or sodium, TM is a transition metal, Ch is a chalcogen element, D is O or B a C1-a , B is selected from at least one type of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one type of negative trivalent anions and negative trivalent anion clusters, 0.5≤x≤8, 0.8≤y≤1.1, 0.25≤a≤0.75, 0.8≤b≤1.2), the crystalline phase of which is basically unable to embed A, but the crystalline phase can be transformed into an amorphous phase after de-A and the transformation is irreversible, and the amorphous phase can reversibly de-embed A.

[0047] In view of the above, this application is hereby filed.

[0048] The present application provides a negative electrode active material, the chemical formula of the negative electrode active material is A x TM y ChD b , where A is lithium and / or sodium, TM is a transition metal, Ch is a chalcogen element, and D is O or B a C 1-a , B is selected from at least one of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one of negative trivalent anions and negative trivalent anion clusters, 0.5≤x≤8, 0.8≤y≤1.1, 0.25≤a≤0.75, 0.8≤b≤1.2; wherein the negative electrode active material has an amorphous phase and the mass proportion of the amorphous phase in the negative electrode active material is not less than 10%.

[0049] The term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. A being Li and / or Na can represent: the existence of Li alone, the existence of Li and Na at the same time, and the existence of Na alone. It is understandable that the choice of A can be based on common choices in actual applications. When the antiperovskite material is used as a positive electrode active material in a battery, when the battery is a lithium-ion battery, A is Li, and when the battery is a sodium-ion battery, A is Na. It should be noted that in this application, alone / means or. For the sake of ease of description, the following description is based on the example of A being Li and the battery being a lithium-ion battery.

[0050] A cluster is a relatively stable microscopic or submicroscopic aggregate composed of several or even thousands of atoms, molecules or ions through physical or chemical binding forces. Anionic clusters refer to clusters that ultimately present a negative valence state.

[0051] B is selected from at least one type of negative monovalent anions and negative monovalent anion clusters, which means that B is a negative monovalent anion and / or a negative monovalent anion cluster. It can be understood that there are many types of negative monovalent anions and there are also many types of negative monovalent anion clusters. B can be a combination of one or more of a variety of negative monovalent anions and a variety of negative monovalent anion clusters. Similarly, C can be a combination of one or more of a variety of negative trivalent anions and a variety of negative trivalent anion clusters.

[0052] The negative electrode active material has an amorphous phase and the mass proportion of the amorphous phase in the negative electrode active material is not less than 10% means: the negative electrode active material is all amorphous, or part of the negative electrode active material is an antiperovskite crystalline phase, and the rest is an amorphous phase, and the mass proportion of the amorphous phase is ≥10%. The mass proportion of the amorphous phase can be obtained by normalizing the characteristic peaks of each phase and calculating the percentage of the characteristic peaks of the amorphous phase as the percentage content of the corresponding phase; at the same time, combined with the transmission electron microscope TEM test, the ratio of the crystalline phase and the amorphous phase structure can be determined by atomic-level morphology characterization.

[0053] It should be noted that after the negative electrode active material mentioned in the present application is applied to the negative electrode sheet to assemble into a battery, the amorphous phase can reversibly deintercalate lithium, and at this time, as the negative electrode active material delithiums during the discharge process of the battery, the crystalline phase will eventually be completely converted into an amorphous phase, and the crystalline phase conversion is irreversible, that is, even if the negative electrode active material is subsequently delithiated, the amorphous phase will not be converted into a crystalline phase, but when it is all crystalline phase, it is difficult to insert lithium and cannot be used as a negative electrode active material. Therefore, the mass proportion of the amorphous phase in the negative electrode active material is not less than 10%, which refers to the initial state of the material, that is, the state before feeding. The negative electrode active material is used in the battery system, and the amorphous phase content will change after charge and discharge cycles.

[0054] The negative electrode active material provided in the present application has an amorphous phase and the mass proportion of the amorphous phase in the negative electrode active material is not less than 10%. On the one hand, the amorphous material has the isotropic volume change characteristic, which can significantly reduce stress concentration. At the same time, the microstructure is relatively loose, which can alleviate volume expansion. In addition, ions do not need to cross grain boundaries in the amorphous material and can move more easily in the amorphous structure, which is beneficial to increase the ion diffusion rate. In addition, due to its amorphous structure, the amorphous material can accommodate more lithium / sodium ions and increase the battery capacity. On the other hand, the anti-perovskite or double anti-perovskite amorphous material of the above general formula has good stability and safety under different lithium deintercalation states, reacts mildly with water, does not burn or explode, and has no toxic or harmful products. It can be used in water-degradable batteries or water-soluble batteries in environments containing water or aqueous solutions, such as water-degradable batteries or water-soluble batteries in oceans and humid environments.

[0055] Illustratively, x is any value among 1, 1.2, 1.5, 1.7, 2, 2.3 or 2.5 or between any two values, y is any value among 0.8, 0.9, 1, 1.1, 1.2 or between any two values, a is any value among 0.25, 0.35, 0.45, 0.55, 0.65, 0.75 or between any two values, and b is any value among 0.8, 0.9, 1, 1.1, 1.2 or between any two values.

[0056] Optionally, the mass proportion of the amorphous phase in the negative electrode active material is not less than 30%, and further optionally not less than 50%.

[0057] Optionally, the negative electrode active material is in an amorphous phase.

[0058] That is, the negative electrode activity is entirely in the amorphous phase.

[0059] In some optional embodiments, 1.9≤x≤2.1; and / or, 0.9≤y≤1.1; and / or, 0.45≤a≤0.55; and / or, 0.9≤b≤1.1.

[0060] Within the above range, adjusting the structure of the negative electrode active material by means of element ratio is beneficial to further improving the capacity of the battery made of the negative electrode active material.

[0061] Optionally, D is O, b=1; or, D is B a C 1-a , 1≤x≤2.5, which can be optionally 1.9≤x≤2.1.

[0062] That is, when D is O, b=1, the chemical formula of the negative electrode active material is A x TM y ChO. When D is B a C 1-a When the negative electrode active material has the general chemical formula A x TM y Ch(B a C 1-a ) b , where 1≤x≤2.5, which can be optionally 1.9≤x≤2.1.

[0063] In some optional embodiments, the TM includes at least one of Fe, Co, Mn, Ni, Cu, Cr, V, Ti, W, Si, Sn, Nb and Mg.

[0064] In some optional embodiments, Ch includes at least one of S, Se and Te.

[0065] Optionally, B includes F - , Cl - Br - ,I - , H - OH - 、BH4 - NH2 - 、NO2 - and CN - At least one of.

[0066] Optionally, C includes N 3- 、(PO4)3- 、(SbO4) 3- and (AsO4) 3- At least one of.

[0067] The above-mentioned N element has a high abundance in the earth, which can reduce the material cost and the cost of the battery. The above-mentioned anion clusters have a stable structure, which is conducive to improving the stability of the antiperovskite material.

[0068] Optionally, the negative electrode active material includes LiFeSO, Li3FeSO, Li5FeSO or Li2FeTe(N 0.5 Cl 0.5 ).

[0069] There are many methods for preparing the above-mentioned negative electrode active materials, such as ball milling solid phase synthesis method and mechanical alloying pre-lithiation method.

[0070] Among them, the ball milling solid phase synthesis method refers to the process of placing each raw material in a high-energy or high-speed planetary ball mill to provide energy for a chemical reaction to occur, thereby preparing an amorphous phase. Taking LiFeSO as an example, Li2O, Fe2O3 and Fe2S3 are used as raw materials, weighed according to a certain stoichiometric ratio, and then mechanically ground in a high-energy or high-speed planetary ball mill to obtain an amorphous lithium-poor negative electrode LiFeSO.

[0071] The mechanical alloying pre-lithium method includes: placing molten metallic lithium and crystalline active materials in a tantalum crucible under the protection of an inert gas, using a magnetic stirrer or a ball mill to perform ball milling / stirring reactions, and obtaining an amorphous lithium-rich negative electrode at the active material level.

[0072] However, the inventors found that the negative electrode active material prepared by ball milling solid phase synthesis method has a relatively low degree of amorphization on the one hand, and a significantly reduced first coulombic efficiency of the battery on the other hand. The possible reason is that the material particles prepared by ball milling solid phase synthesis method are small and have more surface defects, which leads to the irreversible reaction of some lithium entering these defective positions during the first lithium insertion, resulting in a high amount of lithium insertion in the first cycle, reducing the first coulombic efficiency. The mechanical alloy pre-lithium method cannot prepare lithium-poor negative electrodes.

[0073] Therefore, the present application also provides an electrochemical preparation method of the above-mentioned negative electrode active material, the preparation method comprising: obtaining an antiperovskite material characterized by a chemical general formula, performing an amorphization treatment on the antiperovskite material to obtain a negative electrode active material;

[0074] The amorphization treatment includes: making a working electrode by mixing an antiperovskite material and a conductive agent, assembling it with a counter electrode into a liquid half-cell, and then charging the liquid half-cell with a constant current to remove element A to obtain an amorphous phase, wherein element A is Li and the counter electrode is lithium metal, or element A is Na and the counter electrode is lithium metal.

[0075] Since the above-mentioned amorphization treatment is to use the prepared antiperovskite material with good crystal structure that has not been amorphized as the positive electrode of the half-cell, the above-mentioned antiperovskite material is accompanied by lithium delithiation during the charging process of the half-cell, so that it is transformed from a crystalline phase to an amorphous phase and the transformation is irreversible. Therefore, the antiperovskite material can be amorphized by the above-mentioned method, and the negative electrode active material obtained by the above-mentioned method can exist stably and undergo electrochemical reactions compared to the negative electrode active material prepared by the ball milling solid phase method, and the first coulomb efficiency is significantly improved, and the battery cycle stability is effectively enhanced.

[0076] It should be further explained that, since the amorphous phase is prepared by the above-mentioned electrochemical delithiation method, the negative electrode active material obtained by the delithiation method is a lithium-poor / sodium phase. Therefore, in some optional embodiments, the preparation method also includes: performing constant current discharge on the liquid half-cell that obtains the amorphous phase to obtain a lithium-rich / sodium negative electrode active material.

[0077] That is, by performing constant current discharge on the liquid half-cell to obtain the amorphous phase and inserting lithium into the negative electrode active material of the lithium-poor / sodium phase, a lithium-rich / sodium-rich negative electrode active material can be obtained.

[0078] It is understandable that after the amorphization treatment, the liquid half-cell can be removed to obtain the amorphized antiperovskite material as the negative electrode active material. Usually, after the liquid half-cell is removed, the conductive additive and the amorphized antiperovskite are not screened. Generally, when preparing electrode materials, a certain proportion of active substances, conductive agents, and binders are required. Because the obtained amorphized antiperovskite active material already contains a certain proportion of conductive additives, when preparing electrode materials in the subsequent process, the proportion of conductive additives can be reduced.

[0079] It is understandable that after the amorphization treatment, the liquid half-cell can be removed to obtain the negative electrode plate containing the amorphized antiperovskite material for subsequent battery preparation and testing. The liquid half-cell can be made in the form of a mold battery, using a specially customized mold with gaskets and springs to apply pressure to fix the battery material and structure. At this time, no binder is added to the electrode material; whether to add a conductive agent is determined based on the electronic conductivity of the material. If no conductive agent is added, after the mold battery test is completed, it is disassembled and the electrolyte is removed to obtain an amorphous antiperovskite negative electrode material.

[0080] Since it is difficult to directly synthesize amorphous lithium-poor LiFeSO by high-temperature solid-phase method, but it can be synthesized by low-temperature + ball milling method, it shows that LiFeSO is a metastable phase and difficult to prepare by high-temperature solid-phase method. Therefore, it can be reasonably expected that in addition to the above-mentioned electrochemical delithiation method to prepare amorphous phase, amorphization treatment can also be used on the basis of high-temperature solid-phase synthesis method, and rapid cooling can also be used to stabilize the metastable phase.

[0081] The present application also provides a pole piece, which includes an active material layer, and the active material layer includes the above-mentioned negative electrode active material.

[0082] It can be understood that when the electrode sheet is a negative electrode sheet, the active material layer is a negative electrode active material layer, which includes the negative electrode active material used as the electrode material mentioned above.

[0083] The present application also provides a battery, which includes the above-mentioned negative electrode active material, or the above-mentioned electrode sheet.

[0084] It should be noted that in actual application, when the negative electrode sheet contains the above-mentioned negative electrode active material, it can be used according to A x TM y ChD b The value of x in the middle matches the positive electrode material. For example, when it is a lithium-poor phase LiFeSO, it needs to match a lithium-containing positive electrode material, such as LiFePO4, LiCoO2, etc. When it is a lithium-rich phase Li5FeSO, it can match a lithium-poor or lithium-free positive electrode material, such as S positive electrode, FeF3, etc.

[0085] The battery can be a primary battery or a secondary battery; it can be a sodium ion battery or a lithium ion battery; it can be a liquid battery, an all-solid battery or a semi-solid battery. When it is a liquid battery, since the negative electrode active material can be dissolved in water, the electrolyte should be a non-aqueous electrolyte.

[0086] Optionally therefore, the battery comprises a water degradable battery.

[0087] Water-degradable batteries mean that the batteries can dissolve and become ineffective when exposed to water.

[0088] The amorphous negative electrode active material has good stability and safety under different lithium insertion and deintercalation states. It reacts mildly with water, does not burn or explode, and has no toxic or harmful products. It is strongly alkaline after dissolution, forming a local environment that is prone to corrosion in the solution. After a certain period of time, all battery materials (positive and negative electrodes and solid electrolytes, copper foil, aluminum foil) dissolve or corrode, causing the entire battery to degrade and fail in water. Therefore, it can be used in water-degradable batteries in marine and humid environments.

[0089] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0090] It should be noted that the binder is mainly used to bind the various components of the electrode, such as active materials, conductive agents, current collectors, etc., together to form a stable electrode structure. The Li2FeSO / Li liquid half-cell, the first LiFeSO||Li half-cell, the second LiFeSO||Li half-cell and the third LiFeSO||Li half-cell in the following embodiments all use molds to assemble liquid half-cells, that is, unlike traditional button batteries, which require the electrode material to be coated on the current collector, the active material is mixed with the conductive carbon and placed in a mold for pressing, so no binder is required.

[0091] Example 1

[0092] This embodiment provides a negative electrode active material with a chemical formula of LiFeSO. The preparation method of the negative electrode active material includes: using Li2O, Fe2O3 and Fe2S3 as raw materials, mixing 50% Li2O, 17% Fe2O 3、 33% Fe2S3 was weighed and ball-milled at a ball-milling speed of 500 rpm for 8 h in a high-energy planetary ball mill to obtain an amorphous lithium-poor negative electrode LiFeSO.

[0093] Figure 1 The XRD pattern of the negative electrode active material prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the negative electrode active material prepared in Example 1 has an amorphous phase, and the amorphous phase accounts for 60%.

[0094] Example 2

[0095] This embodiment provides a negative electrode active material having a chemical formula of LiFeSO, and a method for preparing the negative electrode active material includes:

[0096] The raw materials Li2O, Fe powder, and S powder were weighed in equal proportions, put into a mortar and ground and mixed for 30 minutes, and the obtained powder was pressed into a sheet, put into a quartz tube, and evacuated to 10 -4 Pa, use hydrogen-oxygen flame to seal the tube, and perform heat treatment in a closed environment under vacuum conditions. The heat treatment temperature is 750 ° C, the temperature is increased at 3 ° C / min, and the temperature is kept constant for 10 hours. After the heat treatment, the obtained precursor is quenched to obtain Li2FeSO.

[0097] 90% Li2FeSO is used as the electrode active material and 10% conductive carbon is mixed as the working electrode, and metal lithium is used as the counter electrode to assemble the Li2FeSO / Li liquid half-cell. When the Li2FeSO / Li liquid half-cell is charged to 227mAh / g at a constant current on a charge-discharge instrument, the positive electrode active material component is the amorphous lithium-poor negative electrode LiFeSO.

[0098] Figure 2 The XRD pattern of the negative electrode active material prepared in Example 2 is shown in FIG. Figure 2 It can be seen that the negative electrode active material prepared in Example 2 has an amorphous phase. Figure 1 , Figure 2 There are still a small number of weaker diffraction peaks in the sample, and the degree of amorphization is relatively low, with the amorphous phase accounting for 30%.

[0099] Example 3

[0100] This embodiment provides a negative electrode active material with a chemical formula of Li5FeSO. The preparation method of the negative electrode active material is different from that of Example 2 only in that when the Li2FeSO4 / Li liquid half-cell is discharged at a constant current to 965 mAh / g on a charge and discharge instrument, the positive electrode active material component is an amorphous lithium-poor negative electrode Li5FeSO4.

[0101] Figure 3 The XRD pattern of the negative electrode active material prepared in Example 3 is shown in FIG. Figure 3 It can be seen that the prepared negative electrode active material has a very low degree of amorphization, no obvious diffraction peak, and the amorphous phase accounts for 90%.

[0102] Example 4

[0103] This embodiment provides a negative electrode active material with a chemical formula of Li3FeSO. The preparation method of the negative electrode active material is different from that of Example 2 only in that when the Li2FeSO4 / Li liquid half-cell is discharged at a constant current to 482 mAh / g on a charge and discharge instrument, the positive electrode active material component is an amorphous lithium-poor negative electrode Li3FeSO4.

[0104] The XRD pattern of the negative electrode active material prepared in Example 4 is Figure 3 Similarly, the prepared negative electrode active material has a very low degree of amorphization, no obvious diffraction peak, and the amorphous phase accounts for 90%.

[0105] Example 5

[0106] This embodiment provides a chemical formula of Li 1.2The preparation method of the negative electrode active material is different from that of Example 2 in that: when the Li2FeSO4 / Li liquid half-cell is discharged at a constant current to 185 mAh / g on a charge and discharge instrument, the positive electrode active material component is an amorphous lithium-poor negative electrode Li 1.2 FeSO4.

[0107] Figure 4 This is the XRD diagram of the negative electrode active material prepared in Example 5. The data show that the prepared negative electrode active material has a high degree of amorphization, has obvious diffraction peaks, and the amorphous phase accounts for 15%.

[0108] Example 6

[0109] The present embodiment provides a mixed negative electrode active material with a chemical formula of Li2FeSO+Li3FeSO. 80% Li2FeSO and 20% Li3FeSO are ball-milled at a low speed for 300 minutes to be fully mixed. When the mixed negative electrode active material is charged and discharged, Li3FeSO plays a major role in the initial lithium insertion stage, and Li2FeSO begins to play a role in the subsequent lithium removal process, and the crystalline phase of Li2FeSO gradually transforms into the amorphous phase of Li 2-x FeSO4.

[0110] Example 7

[0111] This embodiment provides a chemical formula of Li2FeTe(N 0.5 Cl 0.5 ) is a negative electrode active material, and its preparation method comprises: weighing raw materials LiCl, Li3N, Fe powder and Te powder according to the stoichiometric ratio, putting them into a mortar and grinding and mixing them for 30 minutes, pressing the obtained powder into a sheet, putting it into a quartz tube, and evacuating it to 10 -4 Pa, the tube was sealed with hydrogen-oxygen flame, and heat treatment was carried out in a closed environment under vacuum conditions. The heat treatment temperature was 850°C, the temperature was increased at 3°C / min, and the temperature was kept constant for 10 hours. After the heat treatment, the obtained precursor was quenched to obtain Li2FeTe(N 0.5 Cl 0.5 ).

[0112] The negative electrode active material and lithium metal are assembled into a button half-cell, which is recorded as

[0113] Li2FeTe(N 0.5 Cl 0.5 )||Li half-cell, using 0.1C current for charge and discharge, the charge and discharge curve is as follows Figure 5 As shown, it can be seen that the first cycle discharge specific capacity is 372 mAh / g, the first cycle charge specific capacity is 276 mAh / g, and the coulombic efficiency is 74%.

[0114] Comparative Example 1

[0115] The preparation method of Li2FeSO provided in Comparative Example 1 includes:

[0116] The raw materials Li2O, Fe powder and S powder were weighed in equal proportions, put into a mortar and ground for 30 min. The obtained powder was pressed into 10 mm discs, put into a quartz tube, and evacuated to 10 -4 Pa, use hydrogen-oxygen flame to seal the tube, and perform heat treatment in a closed environment under vacuum conditions. The heat treatment temperature is 750 ° C, the temperature is increased at 3 ° C / min, and the temperature is kept constant for 10 hours. After the heat treatment, the obtained precursor is quenched to obtain Li2FeSO.

[0117] Figure 6 The XRD diagram of Li2FeSO prepared in Comparative Example 1 shows that the Li2FeSO synthesized in high temperature solid phase in Comparative Example 1 has obvious diffraction peaks, high crystallinity, and a typical antiperovskite structure.

[0118] Comparative Example 2

[0119] The preparation method of Li2FeSeO provided in Comparative Example 2 includes:

[0120] The raw materials Li2O, Fe powder, and Se powder were weighed in equal proportions, put into a mortar and ground for 30 min, and the obtained powder was pressed into 10 mm discs, put into a quartz tube, and evacuated to 10 -4 Pa, use hydrogen-oxygen flame to seal the tube, and perform heat treatment in a closed environment under vacuum conditions. The heat treatment temperature is 750 °C, the temperature is increased at 3 °C / min, and the temperature is kept constant for 10 h. After the heat treatment, the obtained precursor is quenched to obtain Li2FeSeO.

[0121] Figure 7 This is the XRD diagram of Li2FeSeO prepared in Comparative Example 2. It can be seen that the Li2FeSeO synthesized in high temperature solid phase in Comparative Example 2 has obvious diffraction peaks, high crystallinity, and a typical antiperovskite structure.

[0122] Comparative Example 3

[0123] The preparation method of Li2CoSeO provided in Comparative Example 2 includes:

[0124] The raw materials Li2O, Co powder, and Se powder were weighed in equal proportions, put into a mortar and ground for 30 min, and the obtained powder was pressed into a 10 mm original sheet, placed in a quartz tube, and evacuated to 10 -4Pa, use hydrogen-oxygen flame to seal the tube, and perform heat treatment in a closed environment under vacuum conditions. The heat treatment temperature is 750°C, the temperature is increased at 3°C / min, and the temperature is kept constant for 10 hours. After the heat treatment, the obtained precursor is quenched to obtain Li2CoSeO.

[0125] Figure 8 This is the XRD diagram of Li2CoSeO prepared in Comparative Example 3. It can be seen that the Li2CoSeO synthesized in high temperature solid phase in Comparative Example 3 has obvious diffraction peaks, high crystallinity, and a typical antiperovskite structure.

[0126] Comparative Example 4

[0127] The preparation method of amorphous LiFeSO provided in Comparative Example 4 includes:

[0128] The raw materials Li2O, Fe powder and S powder were weighed at 20%, 40% and 40%, put into a mortar and ground for 30 minutes. The obtained powder was pressed into 10 mm discs, put into a quartz tube and evacuated to 10 -4 Pa, a hydrogen-oxygen flame is used to seal the tube, and a heat treatment is performed in a closed environment under vacuum conditions. The heat treatment temperature is 750°C, the temperature is increased at 3°C / min, and the temperature is kept constant for 10 hours. After the heat treatment, the obtained precursor is quenched to obtain LiFeSO.

[0129] Fig. 9 The XRD diagram of LiFeSO prepared in Comparative Example 4 shows that the LiFeSO synthesized in the high-temperature solid phase in Comparative Example 4 has obvious diffraction peaks. Comparative Example 4 contains more highly crystalline impurities, that is, it is difficult to directly synthesize lithium-poor phase LiFeSO by the high-temperature solid phase method, and the amorphous content is only 10%.

[0130] Comparative Example 5

[0131] The preparation method of Li2FeSO provided in Comparative Example 5 includes:

[0132] The raw materials Li2O, Fe powder, and S powder were weighed in equal proportions, put into a mortar and ground and mixed for 30 minutes, and the obtained powder was placed in a crucible and transferred to a tube furnace. The vacuum was evacuated to -0.05Mpa, He gas was filled at 60ml / min, and the temperature was increased to 750℃ at 3℃ / min, and the temperature was kept constant for 10h. After the sintering process was completed and the furnace was cooled to room temperature, the graphite crucible was quickly transferred to a glove box to avoid excessive contact of the sample with air to obtain Li2FeSO powder.

[0133] Fig.10 The XRD pattern of Li2FeSO prepared in Comparative Example 5 has obvious diffraction peaks, high crystallinity, and a typical antiperovskite structure.

[0134] Test Example 1

[0135] 90% of LiFeSO prepared in Comparative Example 4 was mixed with 10% of conductive carbon to form a working electrode, and metallic lithium was used as a counter electrode to assemble a liquid half-cell, which was recorded as the first LiFeSO||Li half-cell.

[0136] The LiFeSO prepared in Example 1 and the conductive carbon were mixed in 90% and 10% by mass respectively to form a working electrode, and metallic lithium was used as a counter electrode to assemble a liquid half-cell, which was recorded as the second LiFeSO||Li half-cell.

[0137] Assembled in the same manner as above, the LiFeSO prepared in Example 2 corresponds to the third LiFeSO||Li half-cell, and the Li3FeSO prepared in Example 4 corresponds to the Li3FeSO||Li half-cell.

[0138] The above half-cells were charged and discharged at 25°C and 0.1C constant current.

[0139] Fig.11 is the charge and discharge curve of the first LiFeSO||Li half-cell. Fig.11 It can be seen that the charge and discharge specific capacity is significantly lower than that of the second and third LiFeSO||Li half-cells, and the discharge specific capacity is only 85 mAh / g. The overall performance is significantly reduced, indicating that the use of high-temperature solid-phase method to prepare amorphous LiFeSO is very poor.

[0140] Fig.12 is the charge and discharge curve of the second LiFeSO||Li half-cell, according to Fig.12 It can be seen that its first-cycle discharge capacity is relatively high, reaching 1144 mAh / g, but the charging capacity is only 886 mAh / g, and the first coulombic efficiency is relatively low. This is because the amorphous lithium-poor phase LiFeSO in Example 1 is prepared by low-temperature ball milling, and the material particles are small and have more surface defects. During the first-cycle lithium insertion process, part of the lithium will enter these defective positions and undergo irreversible reactions, resulting in a high amount of lithium insertion in the first cycle and a first efficiency as low as 77%.

[0141] Fig.13 is the charge and discharge curve of the third LiFeSO||Li half-cell, according to Fig.13 It can be seen that the discharge capacity reaches 933mAh / g, the charging capacity is only 876mAh / g, the first coulombic efficiency is increased to 94%, and the capacity retention rate is higher than 80% when the half-battery is cycled to 20 cycles. The working electrode after the cycle is subjected to XRD test. Compared with the uncycled amorphous material, the peak position and peak width are almost the same, indicating that the amorphous state prepared by the electrochemical method can exist stably and carry out electrochemical reactions.

[0142] Fig.14 This is the first cycle charge and discharge curve of the Li5FeSO||Li half-cell. It can be seen that its reversible capacity in the voltage range of 0.1-3V is also as high as over 800mAh / g.

[0143] That is, the negative electrode active material prepared in the above embodiment has a high capacity.

[0144] Test Example 2

[0145] 90% LiFeSO prepared in Example 2 was mixed with 10% conductive carbon as the working electrode, and metallic sodium was used as the counter electrode to assemble a liquid half-cell, which was recorded as LiFeSO||Na half-cell. The half-cell was charged and discharged at 25°C and 0.1C constant current. The electrolyte used was sodium electrolyte, and the Na + LiFeSO does not contain sodium. After being assembled with metallic sodium, the battery can be charged and discharged normally, indicating that sodium can be reversibly deintercalated in the material.

[0146] Fig.15 This is the first cycle charge and discharge curve of the Li5FeSO||Na half-cell. It can be seen that its reversible capacity in the voltage range of 0.1-2.8V is as high as 340mAhg -1 above.

[0147] Test Example 3

[0148] The Li3FeSO prepared in Example 4 was used as the negative electrode active material, Li3YCl3Br3 was used as the solid electrolyte, and LiCoO2 was used as the positive electrode active material to assemble an all-solid-state full battery, recorded as LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state full battery.

[0149] The LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state battery is charged and discharged at a constant current of 0.1C.

[0150] Fig.16 This is the first cycle charge and discharge curve of LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state battery under 60℃ test conditions in the voltage range of 0.5-4.2V. Fig.16 It can be seen that the charging capacity is 3.05mAh, the gram capacity reaches 198.63mAh / g, the discharge capacity can reach 3.18mAh, the gram capacity is 227.00mAh / g, the first-cycle coulomb efficiency is 104%, and the average discharge voltage is 2.3214V.

[0151] Fig.17This is the first cycle charge and discharge curve of LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state battery under 60℃ test conditions in the voltage range of 0-4.6V. Fig.17 It can be seen that its charging capacity is 3.34mAh, the gram capacity reaches 209.27mAh / g, the discharge capacity can reach 3.35mAh, the gram capacity is 239.17mAh / g, the first-cycle coulomb efficiency is 114%, and the average discharge voltage is 2.1902V. Compared with the test conditions in the voltage range of 0.5-4.2V, the charge and discharge capacity is slightly improved.

[0152] Fig.18 This is the charge and discharge cycle curve of the LiCoO2||Li3YCl3Br3||Li3FeSO all-solid-state full battery under the test condition of 60℃ and the voltage range of 0.5-4.2V. It can be seen that under the test condition of 60℃ and the voltage range of 0.5-4.2V, the capacity retention rate is 65% after the battery is cycled for 10 weeks, and the capacity retention rate can reach 53% after 20 weeks of cycling.

[0153] Test Example 3

[0154] Due to the different lithium-deintercalation states of the antiperovskite electrode materials in Comparative Examples 1-4 and Examples 1-4, they react mildly with water without burning or exploding. The aqueous solution is green after the reaction, and the reaction product is dried and tested to be amorphous powder particles.

[0155] Therefore, the Li3FeSO prepared in Example 4 is used as the negative electrode active material, the antiperovskite Li2OHCl is used as the solid electrolyte, and the lithium cobaltate LiCoO2 is used as the positive electrode active material to assemble the all-solid-state battery LiCoO2||Li2OHCl||Li3FeSO. After the all-solid-state battery LiCoO2||Li2OHCl||Li3FeSO is immersed in an aqueous solution, the solid electrolyte and the negative electrode active material in the battery dissolve and fail. Since Li3FeSO and Li2OHCl are strongly alkaline when dissolved in water, a local environment that is easy to corrode is formed in the solution. After a certain period of time, all materials (positive and negative electrodes and solid electrolytes, copper foil, and aluminum foil) of the all-solid-state battery LiCoO2||Li2OHCl||Li3FeSO are dissolved or corroded, causing the entire battery to degrade and fail in water.

[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A negative electrode active material, characterized in that: The chemical formula of the negative electrode active material is A x TM y ChD b , where A is lithium and / or sodium, TM is a transition metal, Ch is a chalcogen element, and D is O or B a C 1-a , B is selected from at least one of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one of negative trivalent anions and negative trivalent anion clusters, 0.5≤x≤8, 0.8≤y≤1.1, 0.25≤a≤0.75, 0.8≤b≤1.2; The negative electrode active material has an amorphous phase and the mass proportion of the amorphous phase in the negative electrode active material is not less than 10%.

2. The negative electrode active material according to claim 1, characterized in that The mass proportion of the amorphous phase in the negative electrode active material is not less than 30%; Optionally, the negative electrode active material is in an amorphous phase.

3. The negative electrode active material according to claim 1, characterized in that 1.9≤x≤2.1; and / or, 0.9≤y≤1.1; and / or, 0.45≤a≤0.55; and / or, 0.9≤b≤1.

1.

4. The negative electrode active material according to claim 1, characterized in that The D is O, b=1; Or, the D is B a C 1-a , 1≤x≤2.5, which can be optionally 1.9≤x≤2.

1.

5. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The TM includes at least one of Fe, Co, Mn, Ni, Cu, Cr, V, Ti, W, Si, Sn, Nb and Mg.

6. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The Ch includes at least one of S, Se and Te; Optionally, said B includes F - , Cl - Br - ,I - , H - OH - 、BH4 - NH2 - 、NO2 - and CN - at least one of; Optionally, the C includes N 3- 、(PO4) 3- 、(SbO4) 3- and (AsO4) 3- At least one of.

7. The method for preparing a negative electrode active material according to any one of claims 1 to 6, characterized in that: include: Obtaining an antiperovskite material characterized by the chemical formula, and performing an amorphization treatment on the antiperovskite material to obtain the negative electrode active material; The amorphization treatment includes: mixing the antiperovskite material and a conductive agent to make a working electrode, assembling it with a counter electrode into a liquid half-cell, and then performing constant current discharge on the liquid half-cell to remove element A to obtain the amorphous phase, wherein element A is Li and the counter electrode is lithium metal, or element A is Na and the counter electrode is lithium metal.

8. The preparation method according to claim 7, characterized in that: The preparation method further comprises: performing constant current charging on the liquid half-cell that obtains the amorphous phase to obtain the negative electrode active material rich in lithium / sodium.

9. A pole piece, characterized in that: The invention comprises an active material layer, wherein the active material layer comprises the negative electrode active material according to any one of claims 1 to 6.

10. A battery, characterized in that: The battery comprises the pole piece as claimed in claim 9; Optionally, the battery comprises a water-degradable battery.

Citation Information

Patent Citations

  • Lithium-enriched anti-perovskite sulfides, solid electrolyte material containing lithium-enriched anti-perovskite sulfides and application of solid electrolyte material

    CN104466239A

  • Preparation method of electrolyte of all-solid-state lithium battery

    CN111446493A

  • Amorphous material and method for producing same, crystalline material and method for producing same, positive electrode, battery, battery pack, and vehicle

    JP2017154944A